Zones of Re-membering. - GIFFORD, DON (Consciousness, Literature & the Arts (1573-2193), 2011)
The article discusses memory as a passive reception of sense impression on the brain, conceived as a "tabula rasa" or blank sheet to be arranged by "hosts of busy, anonymous archivist." It claims that contrary to the Freudian version of the Lockean hypothesis and the mechanistic theories of neurosurgeons, memory is not machine-like. Rather, the article espouses that remembering does not move like an arrow, but more like a river, that moves erratically backwards and forwards, filled with ebbs and flows, rapids and shallows.